THE EFFECT OF WORKLOAD ON JOB SATISFACTION WITH MEDIATION OF JOB STRESS AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) (STUDY ON EMPLOYEES OF PT X) - Farhiya, Daniyatul; Noermijati Noermijati; Nur Prima Waluyowati (CV. Radja Publika, 2023)
This research sought to investigate the association between workload and job satisfaction in PT X employees, as well as how job stress also moderated the association were organizational citizenship behavior. The data collection method was an online questionnaire, with a saturated sample of 135 employees of PT X. Explanatory and quantitative research approaches were used in SEM-PLS 3.0 analysis of the data. The investigation's findings indicate that being overly busy has a detrimental influence on work satisfaction. Workload significantly reduces stress at work. Job satisfaction is significantly impacted negatively by job stress. Organizational citizenship behavior is negatively impacted by workload. Organizational citizenship activity has a considerable beneficial influence on job satisfaction. Work-related stress has a strong moderating effect on the association between workload and job satisfaction. The modulation of the relationship between workload and job satisfaction is greatly influenced by organizational citizenship behavior.